PENERAPAN STRATEGI MANAJEMEN INOVASI DALAM MENINGKATKAN DAYA SAING PERUSAHAAN - Moh. Wahib; Ari Susanto (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
In today's dynamic business landscape, the implementation of innovation management strategies stands as a pivotal effort to enhance company competitiveness. Innovation serves as a cornerstone for creating additional value and sustaining a competitive edge amidst evolving market dynamics. This article delves into the qualitative exploration of how companies deploy innovation management strategies and assesses their impact on organizational performance through insightful case studies. Through a qualitative approach with case studies on several companies, this article explores how innovation management strategies are implemented and their impact on company performance. The findings show that companies that proactively manage the innovation process by implementing appropriate management strategies are able to create products and services that meet market needs, improve operational efficiency, and increase customer satisfaction. The practical implication of this research is the importance of management awareness and commitment to innovation as an integral part of business strategy to ensure the survival and growth of the company amid increasingly fierce competition.